Hubungan Supervisi Kepala Sekolah dengan Kinerja Guru SMK Bina Cendekia Kecamatan Leuwiliang Kabupaten Bogor - Nurajiah; Rusdiono mukri; Joko Trimulyo (Institut Agama Islam Sahid (INAIS) Bogor, 2019)
This study aims to determine the relationship between principal supervision and teacher performance at Bina Cendekia Vocational High School, Leuwiliang District, Bogor Regency. Research using descriptive method with a correlational approach. Collecting data using a questionnaire or a questionnaire. The results showed that there was a positive relationship between variable X (supervision of the principal) and variable Y (teacher performance), with a correlation coefficient of 0.455/45%. This figure shows that the relationship between the two variables is categorized as a significant positive relationship with the moderate/sufficient category. Thus it can be stated that the correlation between variable X and variable Y is a moderate or sufficient correlation.